THE INFLUENCE OF INFORMATION ON @KEMENKES_RI INSTAGRAM ACCOUNT TOWARDS MASK PURCHASE DECISIONS AMONG INDONESIAN MILLENNIALS - Dianita, Indria Angga; Camalia, Rizki; Musadad, Musadad; Nurfikria, Ikrima; Maharani, Iris Fatia (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2021)
The Instagram account @kemenkes_ri is the official account of the Ministry of Health of the Republic of Indonesia which has been aggressively disseminating information on health protocols, including about the use of masks, during the Covid-19 pandemic. Along with the appeal to use masks, there is an increasing need to buy masks, including among the Indonesian millennials. Information is what consumers are looking for at an early stage in the purchase decision-making process. Therefore, this study aims to determine the influence of information on the @kemenkes_ri Instagram account towards mask purchase decisions among Indonesian millennials. The method used in this research is quantitative by distributing a survey to 100 respondents of Indonesian millennials. The data collected were analyzed using the Method of Successive Interval (MSI), normality test, homogeneity test, correlation coefficient test, determination coefficient test, simple linear regression analysis, and t test. The results of the analysis show that the information on the @kemenkes_ri Instagram account has a significant positive effect on mask purchase decisions among Indonesian millennials. Based on these results, it can be concluded that information can have an influence on consumer purchase decisions.Â